Generics versus branded generics: A case of confusion - Proteesh Rana; Rachna Gupta (Indian Journal of Community and Family Medicine)
Generic medicines are generally marketed under international nonproprietary names but may also be marketed by a pharmaceutical company under a brand name, i.e. branded generics. The Indian pharmaceutical industry is the leading supplier of unbranded generics to the world but promotes the marketing of branded generics within the country. The same generic medicine is marketed under different brand names at variable prices, which has resulted in a state of confusion among Indian doctors and patients. There is also a false belief that branded generic medicines are more reliable and have better efficacy and safety than unbranded generics. Major regulatory changes are needed to resolve this confusion and apprehension related to the use of unbranded generic medicines.